2002
DOI: 10.1200/jco.2002.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Study of Cisplatin With Gemcitabine or Paclitaxel or Vinorelbine as Induction Chemotherapy Followed by Concomitant Chemoradiotherapy for Stage IIIB Non–Small-Cell Lung Cancer: Cancer and Leukemia Group B Study 9431

Abstract: Four cycles of gemcitabine, vinorelbine, or paclitaxel in combination with cisplatin can be administered at these doses and schedules. The observed survival rates exceed those of previous CALGB trials and may be attributable to the use of concomitant chemoradiotherapy. Induction chemotherapy added to concomitant chemoradiotherapy is being evaluated in a phase III randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
215
2
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(245 citation statements)
references
References 26 publications
20
215
2
9
Order By: Relevance
“…We report that the daily cisplatin and radiotherapy arm yielded the best survival rate, supporting the idea that improving chest disease control will improve survival. In recent years, many other chemotherapeutic agents have been delivered as sensitizing agents to improve radiation effect, including the taxanes, gemcitabine, vinorelbine, and topoisomerase (17,18). Among these, paclitaxel has been a favored drug due to its ability to arrest cells at the G2/M interphase in the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…We report that the daily cisplatin and radiotherapy arm yielded the best survival rate, supporting the idea that improving chest disease control will improve survival. In recent years, many other chemotherapeutic agents have been delivered as sensitizing agents to improve radiation effect, including the taxanes, gemcitabine, vinorelbine, and topoisomerase (17,18). Among these, paclitaxel has been a favored drug due to its ability to arrest cells at the G2/M interphase in the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum-based chemotherapy is the standard for the treatment of young, well-performing patients with metastatic NSCLC [6; 20] and most authors regard the doublet cisplatin (or carboplatin)/paclitaxel as a standard chemotherapy regimen [21][22][23][24]. In chemo-naïve patients, singleagent-paclitaxel has been studied on different The most common toxicity was alopecia (51% in all), neuropathy (never severe), anemia, and leukopenia (never associated with life-threatening infections).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is also crucial to select an appropriate chemotherapeutic regimen. CALGB9431 (22) analyzed the superiority by combining cisplatin with paclitaxel, gemcitabine and NVB, respectively, in concomitant radiochemotherapy. By comparing results, it was found that there was significantly less associated toxicity with NVB than with paclitaxel or gemcitabine with Grade III/IV neutropenia (27, 53 and 51%, respectively), and notably fewer cases of vomiting and anorexia (16, 15, 8% and 22, 27, 12%, respectively).…”
Section: Discussionmentioning
confidence: 99%